Investigation of the k-dimensionality of the LILI-128 cipher Boolean function - Koniushok, S.M. (Radiotekhnika, 2018)
The paper presents results of the experimental study of the k-dimensionality of the LILI-128 cipher Boolean function, which demonstrated the potential for the realization of a statistical attack based on near-proximity of Boolean functions with algebraically degenerate functions.